Kajian Kepuasan Petani Terhadap Atribut Benih Tomat di Kabupaten Bandung - Setiyaningrum, Kayla Amina; Saidah, Zumi (Universitas Galuh, 2024)
An act to increase the production of tomatoes needed since the Indonesian tomatoes production is still fluctuating. One of the efforts is to increase tomatoes’ production is the usage of certified tomatoes’ seed. The research conducted to analyze the farmers’ satisfaction level on the high variety marketed tomatoes’ seed. The research conducted using descriptive analysis method, Important Performance Analysis (IPA) and analysis using Customer Satisfaction Index (CSI). The research conducted in Bandung Regency in the area of Pangalengan Subdistrict and Arjasari subdistrict. The survey included a hundred respondents in total. Sampling conducted using survey method through questioners. Sampling selected using multistage cluster random sampling. Result of the research showed that there are 12 attributes considered as important and good performance according to farmers. The attributes included varieties with high yield (X2.3); varieties with good weather tolerance (heat and rain) (X2.4); varieties with quality that corresponds to the expected quality (X3.1); high productivity (X3.2); amount according to the land area requirement (X4.1); seed delivery to farmers (X4.4); expired date (X5.1); easy to access (X6.1); seed stock availability(X6.2); affordable price (X7.2); price according to the expected quality (X7.3). Farmers’ Satisfaction Analysis Result showed that 70% of farmers satisfied by the attributes of marketed tomatoes’seed.